Pengaruh Social Media Marketing, E-Wom Dan Kualitas Pelayanan Terhadap Keputusan Pembelian (Study Di Kaekopi Lamongan) - Nanto Purnomo; Dedy Fahmi Hakim (Journal on Education, 2024)
This study aims to determine the effect of Social Media Marketing, E-WoM and Service Quality on Purchasing Decisions with a quantitative approach. The population in this study were Kaekopi Lamongan customers and the sample used was 180 respondents. The sample technique used purposive sampling using the Hair formula. Based on the results of the validity and reliability tests of the Social Media Marketing, E-WoM and Service Quality variables, it can be concluded that they are valid and reliable. Based on the results of hypothesis testing, it can be concluded that the variables of Social Media Marketing, E-WoM and Service Quality partially or simultaneously have a significant influence on Purchasing Decisions at Kaekopi Lamongan. The Service Quality variable is the most dominant independent variable in influencing the dependent variable.